PENGUATAN KAPASITAS KOMUNITAS SEBAGAI LEMBAGA PELAYANAN SOSIAL DALAM PENCEGAHAN DAN PENANGGULANGAN DAMPAK SOSIAL TBC PADA MASYARAKAT DI DESA SUKORAMBI KABUPATEN JEMBER - Fajri Maulana; Senato Erasandi; Yaen Miftakhul Laily; Nian Riawati; Wydha Mustika Maharani; Masadib Akmal Vyandri; Muhamad Nanda Al Hakim Akbar; Laili Rahma Halimah; Aryo Prakoso (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
Health problems such as Tuberculosis (TB) are a public health issue in Sukorambi Village that strongly intersects with social issues, because it gives rise to stigma, social isolation, reduces productivity, and increases the economic burden on households. TB is not merely a clinical issue, but a socio-health issue that requires social system support at the village level ranging from education, mentoring, to service referrals. Therefore, the objective of this community service activity is directed at building a community (Karang Taruna and students) as a social service institution capable of supporting the prevention and mitigation of the social impacts of TB more systematically. The approach methods used in this implementation include Observation, Socialization and Focus Group Discussion (FGD). The substantive achievement of the activity can be seen from the formation of a shared understanding of the management framework of community-based social service organizations and this activity succeeded in achieving the main achievement of increasing the capacity of young actors in Sukorambi Village, especially Karang Taruna and students in viewing TB as a social issue that requires a collective community-based response.